Effect of Blended Learning Approach on ESL Students' Hotel English Service Skills and Attitudes towards Active Learning - Ma, Yumei; Julian Robillos , Roderick (Forum for Linguistic Studies, 2025)
This study aims to enhance ESL students'Hotel English service skills, promote active learning, and explore learner experiences using a blended learning approach via the Treenity platform. A Sequential Mixed Methods design combined quantitative pre- and post-tests with questionnaires and qualitative observations and interviews. 49 students from Tourism English majors at Lijiang Normal University taking a Hotel English course participated. The intervention covered three modules based on real-life hotel scenarios aligned with WorldSkills Occupational Standards. Blended learning combined Treenity's asynchronous online tasks with face-to-face role-plays, discussions, and feedback. Results showed significant overall improvement (pre-test M = 43.44, post-test M = 57.79, p = 0.004). The “Checking In” module had the largest gain (pre-test M = 30.03 to post-test M = 66.92), “Checking Out” improved moderately (pre-test M = 43.28 to post-test M = 52.40), while “Room Reservations” declined slightly (pre-test M = 57.02 to post-test M = 54.05), likely due to higher initial scores and task complexity. Student perceptions were positive (M = 4.12, “agree”), valuing Treenity's flexibility and autonomy. Engagement was strong, with 81% spending over 30 minutes on Lesson Plan #3 tasks and 96% participating in group work. Qualitative feedback confirmed the model's effectiveness in providing context-rich, practical learning, though some learners required additional scaffolding. This study contributes novel evidence supporting the integration of blended learning platforms tailored for vocational ESP contexts, demonstrating how combining authentic industry standards with flexible digital tools can significantly improve language proficiency, engagement, and learner autonomy in specialized ESL settings.